Алгоритм розподілу потужності в автономній енергосистемі з асинхронними вентильними генераторами - Мазуренко, Леонід Іванович; Джура, Олександр Васильович; Романенко, Володимир Іванович; Шевчук, Надія Іванівна (НТУ "ХПІ", 2013)
The paper deals with a strategy to control power flow in a stand alone power system which uses two diesel induction generators with short circuited rotor and a storage battery. The semiconductor excitation systems control magnetizing and DC output voltages of the generators. Reference values of the voltages are calculated by an active power flow control block (APFCB). The control strategy of the APFCB enables to reduce fuel consumption comparing to “single diesel“ system of the same power.
Keywords: автономні енергосистеми; вентильне збудження; вихідні потужності АГ; блок контроля розподілу потужності; енергоефективність функціонування АЕ